Pasture intake protects against commercial diet-induced lipopolysaccharide production facilitated by gut microbiota through activating intestinal alkaline phosphatase enzyme in meat geese - Ali, Qasim; Ma, Sen; Farooq, Umar; Niu, Jiakuan; Li, Fen; Li, Defeng; Wang, Zhichang; Sun, Hao; Cui, Yalei; Shi, Yinghua (Frontiers in Immunology, 2022)
Diet strongly affects gut microbiota composition, and gut bacteria can influence the cecal barrier functions and systemic inflammation through metabolic endotoxemia. In-house feeding system (IHF, a low dietary fiber source) may cause altered cecal microbiota composition and inflammatory responses in meat geese via increased endotoxemia (lipopolysaccharides) with reduced intestinal alkaline phosphatase (ALP) production. The effects of artificial pasture grazing system (AGF, a high dietary fiber source) on modulating gut microbiota architecture and gut barrier functions have not been investigated in meat geese. The intestinal ALP functions to regulate gut microbial homeostasis and barrier function appears to inhibit pro-inflammatory cytokines by reducing LPS-induced reactive oxygen species (ROS) production. This study aimed to investigate whether intestinal ALP could play a critical role in attenuating ROS generation and ROS facilitating NF-κB pathway-induced systemic inflammation in meat geese. First, we assessed the impacts of IHF and AGF systems on gut microbial composition via 16 sRNA sequencing in meat geese. In the gut microbiota analysis, meat geese supplemented with pasture showed a significant increase in commensal microbial richness and diversity compared to IHF meat geese, thus demonstrating the antimicrobial, antioxidant, and anti-inflammatory ability of the AGF system. Secondly, host markers analysis through protein expression of serum and cecal tissues and quantitative PCR of cecal tissues was evaluated. A significant increase in intestinal ALP-induced Nrf2 signaling pathway was confirmed representing LPS dephosphorylation mediated TLR4/MyD88 induced ROS reduction mechanisms in AGF meat geese. Further, the correlation analysis of top 44 host markers with gut microbiota showed that artificial pasture intake induced gut barrier functions via reducing ROS-mediated NF-κB pathway-induced gut permeability, systemic inflammation, and aging phenotypes. In conclusion, AGF system may represent a novel therapy to counteract the chronic inflammatory state leading to low dietary fiber-related diseases in animals.